FEATURES OF THE PREVENTION OF EMOTIONAL BURNOUT OF TEACHERS BY ART THERAPY IN THE CONDITIONS OF WAR - Datsun, Olena; Demchenko, Nataliia (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2023)
The article considers one of the actual scientific and practical problems of modern psychological science – prevention of emotional burnout of teachers in war conditions. Ensuring the effectiveness of the process of educational and pedagogical interaction is possible only on condition of preserve of the mental health of all its participants. It is topical in the time of standing of constant stress factors of war. The purpose of the study: to develop new methods of prevention of emotional burnout of teachers by means of art therapy. The following research methods were used to solve the set tasks: analysis of scientific literature; online poll; performance of tasks for reflection, analysis of products of activity of pupils at performance of the developed individual tasks. Results: based on the empirically analysis the putting hypothesis was confirmed that most teachers have a feeling of emotional burnout during the war. The specifics of workload of teaching activities often do not motivate to detailed study of specifics of the display of one’s own emotional state, at the same time they have a desire immediately go to stage of receiving psychological help as classes for the prevention and correction of emotional burnout among teachers. For prevent of emotional burnout among teachers, we have developed a corrective program using art therapy materials. Working conditions during martial law require the search for simple and effective methods for creating new methods. In our opinion, these are the «Methodology of spontaneous drawing using edible materials «Tree», the technique «Spot» and «Thoughts about autumn» developed by us. Conclusions: it is empirically confirmed that in the conditions of war, most teachers experience emotional burnout. The proposed methods of prevention of emotional burnout among teachers can be recommended for use in complex programs of correction and prevention of emotional burnout